The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1097/fbp.0000000000000633
|View full text |Cite
|
Sign up to set email alerts
|

Sodium butyrate enhances fear extinction and rescues hippocampal acetylcholinesterase activity in a rat model of posttraumatic stress disorder

Abstract: It is believed that impaired extinction of fear memories is an underlying cause for the development of posttraumatic stress disorder (PTSD). Histone deacetylases (HDAC) are enzymes that modulate extinction by changing the chromatin structure and altering protein synthesis in the brain. Studies show that stress modifies both HDAC activity and cerebral cholinergic neurotransmission. The present work aims to evaluate the effect of sodium butyrate (NaBu), an HDAC inhibitor, on behavioral markers of extinction and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 70 publications
2
5
0
Order By: Relevance
“…3A ). Cholinergic regulation through AchE modulation is reported in several other investigations( 21 36 37 38 ). We have recently found that reduced hippocampal cholinesterase activity occurs concurrently with extinction and working memory deficits( 36 ) in male rats.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…3A ). Cholinergic regulation through AchE modulation is reported in several other investigations( 21 36 37 38 ). We have recently found that reduced hippocampal cholinesterase activity occurs concurrently with extinction and working memory deficits( 36 ) in male rats.…”
Section: Discussionsupporting
confidence: 59%
“…Cholinergic regulation through AchE modulation is reported in several other investigations( 21 36 37 38 ). We have recently found that reduced hippocampal cholinesterase activity occurs concurrently with extinction and working memory deficits( 36 ) in male rats. The hippocampus receives cholinergic inputs from the medial septum and diagonal band of Broca neurons in the basal forebrain cholinergic nuclei, while the amygdala is innervated by neurons in the nucleus basalis magnocellularis.…”
Section: Discussionsupporting
confidence: 59%
“…Histone deacetylation, mediated by HDACs enzymes, is a typical epigenetic regulatory mechanism involved in learning, memory formation, and stress [ 15 , 19 21 ]. In this regard, neuron-specific over-expression of HDAC2 impaired memory formation in adult mice, whereas HDAC2 deficiency resulted in memory facilitation, like that induced by nonselective HDACs inhibitors treatment [ 1 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that sodium butyrate prevents hypobaric hypoxia-induced spatial memory deficits 14 . In an animal model of posttraumatic stress disorder, sodium butyrate reversed single prolonged stress-induced hippocampal histone deacetylase (HDAC) overexpression and enhanced fear elimination 15 . Further, sodium butyrate improves synaptic plasticity by reducing neuroinflammation in 5XFAD mice early in the disease 16 .…”
Section: Introductionmentioning
confidence: 99%